Equine Incisor Lesions: Histologic Confirmation of Radiographic, Macroscopic, and Micro-Computed Tomographic Findings - Louisa Albers; Astrid Bienert-Zeit; Carsten Staszyk (Veterinary Sciences, 2022)
Equine Odontoclastic Tooth Resorption and Hypercementosis (EOTRH) and other incisor lesions are often diagnosed only in advanced stages. The incisors of 20 horses were examined radiographically, macroscopically, and via micro-computed tomography (µCT) to discriminate EORTH-affected teeth. Five categories from healthy to severely affected teeth were formed and teeth from each category were examined histologically to evaluate the opportunity of earlier radiographic diagnosis. Histologically, odontoclastic resorptive lesions, leukocytic infiltrations, and areas of irregular cementum and granulation tissue were observed. The extent and severity of histological findings were correlated to the µCT data. Micro-CT imaging was suitable to detect subtle irregularities in the dental substances which were referred to as resorptive lesions. Although histological examinations confirmed the presence of resorptive lesions, not all of them were classified as pathological conditions. Instead, repaired surface lesions were documented which were regarded as a physiological condition. Nevertheless, incisors which were radiographically regarded as healthy can also feature histological signs of EOTRH. Therefore, due to the possibility of misinterpreting radiographic findings combined with superimpositions on intraoral radiographs, the detection of early resorptive lesions remains challenging.